Developing a maturity model for government community broadband projects - Bahri, Shamshul; Fauzi, Ali (Inderscience, 2018)
Broadband technology is the latest information and communication technologies (ICT) deployed to address the digital divide phenomenon, especially the divide between the urban and rural areas. Governments all over the world have initiated programs and projects to enabled people in the rural areas to have fast internet access enjoyed by the urban areas. Anecdotal evidence, however, suggests that these programs and projects enjoy different rates of success that requires identification of their reasons. Hence, this study attempts to develop a maturity model for government community broadband projects. This maturity model determines the more successful projects and the reasons for their success compared to the less successful ones. Findings from this study will inform governments who are in the midst of implementing a community broadband project or who are planning to do so.